PENGEMBANGAN DESA AGROINDUSTRI BAWANG MERAH DI DESA TLOGOHAJI KECAMATAN SUMBERREJO KABUPATEN BOJONEGORO - Anisa Ulfah; Zunia Fidya Astutik; Afni Nor Khofifah; Syahruliya Romadloni Wahidah; Faridatun Nikmah (Universitas Mataram, 2022)
Most of the people of Tlogohaji Village are shallot farmers. However, the community's economy is still at the lower middle level. This is because one of them is that the community has not been able to process the harvested shallots so that the people who are mostly farmers directly sell them to collectors. On the other hand, this potential should be used as an opportunity to be developed so that it can improve the welfare of the community through processing shallot agricultural products. Therefore, this community service activity aims to improve community knowledge and skills through community empowerment activities in Tlogohaji Village, Sumberrejo District, Bojonegoro Regency in developing shallot agro-industry villages through a holistic program of village development and empowerment (PHP2D) in 2021. community empowerment activities through PHP2D, including socialization activities for the development of agro-industrial villages, training / counseling on shallot cultivation, shallot processing, marketing of processed shallot products, and processing of onion skin waste. The activity involved village officials, PKK, Karang Taruna, BUMDes, as well as onion farmer groups. Based on the activities carried out, the results obtained through these activities showed that as many as 70% of the people who participated in the activities already had the understanding and skills in developing agro-industrial villages. The achievement of the objectives of the activity is also shown by the community through increasing enthusiasm and positive motivation in processing agricultural shallots into various types of products as an indicator of the development of agro-industrial villages. In addition, the community has the insight and skills in processing and packaging processed shallot products, such as fried onions, chili sauce, and onion powder. This is then used to market processed onion products that have been produced, both online and marketed directly. Thus, the community empowerment activities carried out have been carried out properly according to the expected goals, namely empowering the people of Tlogohaji Village, Sumberrejo District, Bojonegoro Regency so that they have the insight and skills to process and market the results of onion processing.